Local release of metalloproteinases and their inhibitors after a successful revascularisation procedure. Issue 1 (27th October 2019) - Grande, Raffaele; Brachini, Gioia; Sterpetti, Antonio V.; Borrelli, Valeria; Serra, Raffaele; Pugliese, Francesco; D'Ermo, Giuseppe; Tartaglia, Elvira; Rubino, Paolo; Mingoli, Andrea; Sapienza, Paolo
Abstract: An altered balance between metalloproteinases (MMPs) and their inhibitor tissue inhibitor of metalloproteinases (TIMPs) may influence the healing process of a minor amputation following a successful vein graft. To speed up this process, negative pressure wound therapy (NPWT) and advanced moist wound dressing have been proposed. We determined the systemic and local release of MMP‐1, ‐2, ‐3, ‐9, TIMP‐1, and TIMP‐2 by enzyme linked immunosorbent assay (ELISA) technique and their influences in the healing process in 26 patients who underwent minor amputation after a successful revascularisation procedure. Twelve patients (group 1) were medicated with NPWT and 14 (group 2) with advanced moist wound dressing. Plasma samples were collected on the morning of surgery and thereafter at 1, 3, and 5 months; exudates were collected 3 days after surgery when amputation was performed and thereafter at 1, 3, and 5 months. Fifteen age‐matched healthy male volunteers served as controls. All wounds healed in 5 ± 0.5 months. Follow‐up plasma and local release of MMP‐1, ‐2, ‐3, and ‐9 were overall significantly lower when compared with the preoperative levels, while those of TIMP‐1 and ‐2 were significantly higher with no differences among the groups. Despite no differences in the healing process being observed among the two types of medications, at 1 month the local release of MMP‐2 and ‐9 was significantly lower ( P = .013 and .047, respectively) and that of TIMP‐1 was significantly higher ( P = .042) in group 1 as compared to group 2. A correct and aggressive local approach to the wound is able to promote the healing of the lesion stimulating the extracellular matrix turnover with local MMP/TIMP adequate balance and favouring the creation of granulation tissue. However, a successful restoration of an adequate blood flow remains the key point of a durable and rapid wound healing.